Symptomatic treatment of uncomplicated lower urinary tract infections in the ambulatory setting: randomised, double blind trial - Kronenberg, Andreas; Bütikofer, Lukas; Odutayo, Ayodele; Mühlemann, Kathrin; da Costa, Bruno R; Battaglia, Markus; Meli, Damian N; Frey, Peter; Limacher, Andreas; Reichenbach, Stephan; Jüni, Peter (BMJ (Online), 2017)
Objective To investigate whether symptomatic treatment with non-steroidal anti-inflammatory drugs (NSAIDs) is non-inferior to antibiotics in the treatment of uncomplicated lower urinary tract infection (UTI) in women, thus offering an opportunity to reduce antibiotic use in ambulatory care.Design Randomised, double blind, non-inferiority trial.Setting 17 general practices in Switzerland.Participants 253 women with uncomplicated lower UTI were randomly assigned 1:1 to symptomatic treatment with the NSAID diclofenac (n=133) or antibiotic treatment with norfloxacin (n=120). The randomisation sequence was computer generated, stratified by practice, blocked, and concealed using sealed, sequentially numbered drug containers.Main outcome measures The primary outcome was resolution of symptoms at day 3 (72 hours after randomisation and 12 hours after intake of the last study drug). The prespecified principal secondary outcome was the use of any antibiotic (including norfloxacin and fosfomycin as trial drugs) up to day 30. Analysis was by intention to treat.Results 72/133 (54%) women assigned to diclofenac and 96/120 (80%) assigned to norfloxacin experienced symptom resolution at day 3 (risk difference 27%, 95% confidence interval 15% to 38%, P=0.98 for non-inferiority, P<0.001 for superiority). The median time until resolution of symptoms was four days in the diclofenac group and two days in the norfloxacin group. A total of 82 (62%) women in the diclofenac group and 118 (98%) in the norfloxacin group used antibiotics up to day 30 (risk difference 37%, 28% to 46%, P<0.001 for superiority). Six women in the diclofenac group (5%) but none in the norfloxacin group received a clinical diagnosis of pyelonephritis (P=0.03).Conclusion Diclofenac is inferior to norfloxacin for symptom relief of UTI and is likely to be associated with an increased risk of pyelonephritis, even though it reduces antibiotic use in women with uncomplicated lower UTI.Trial registration ClinicalTrials.gov NCT01039545.